2007
DOI: 10.1007/s11604-007-0156-0
|View full text |Cite
|
Sign up to set email alerts
|

Mediastinal lymphatic drainage from pulmonary lobe based on CT observations of histoplasmosis: implications for minimal N2 disease of non-small-cell lung cancer

Abstract: Our data show a predictable pattern of lobar lymphatic drainage to the mediastinum. This may have implications on the minimal N2 disease of non-small-cell lung cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
0
4
0
1
Order By: Relevance
“…Gorai et al 31 suggested that the incidence of skip N2 was significantly associated with pleural involvement in patients with clinical IA NSCLC and in those with nodal metastasis, and assumed an involvement of the subpleural lymphatic drainage. In addition, Takahashi et al 32,33 demonstrated a predictable pattern of lobar lymphatic drainage to the mediastinum by the assessment of CT studies of patients with primary complex histoplasmosis consisting of a single lobe pulmonary lesion and mediastinal nodal disease. They revealed that there were seven of 122 (5.7%) upper-lobe cases with skip SCLN involvement and 14 of 129 (10.8%) lowerlobe cases with skip UMLN involvement in their study.…”
Section: Discussionmentioning
confidence: 99%
“…Gorai et al 31 suggested that the incidence of skip N2 was significantly associated with pleural involvement in patients with clinical IA NSCLC and in those with nodal metastasis, and assumed an involvement of the subpleural lymphatic drainage. In addition, Takahashi et al 32,33 demonstrated a predictable pattern of lobar lymphatic drainage to the mediastinum by the assessment of CT studies of patients with primary complex histoplasmosis consisting of a single lobe pulmonary lesion and mediastinal nodal disease. They revealed that there were seven of 122 (5.7%) upper-lobe cases with skip SCLN involvement and 14 of 129 (10.8%) lowerlobe cases with skip UMLN involvement in their study.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study on 400 patients with pulmonary histoplasmosis consisting of mediastinal node involvement and pulmonary lesions within a single lobe, including multisegmental lesions (18), we assessed the lymphatic drainage pattern to the mediastinum from each lobe but could not disclose segment specific lymphatic drainage pattern. To assess the lymphatic drainage pattern to the mediastinum depending on each pulmonary segment, we collected the CT studies of patients with primary complex of histoplasmosis with solitary pulmonary lesion and hilar and/or mediastinal node involvement in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…In primary infection, pulmonary lesions are commonly solitary and associated with hilar and/or mediastinal nodal disease. In individuals with normal cellular immunity, pulmonary histoplasmosis spontaneously resolves and results in a calcified primary complex consisting of a calcified pulmonary nodule and calcified hilar and/or mediastinal nodes, similar to the Ranke complex of primary tuberculosis (18). Therefore, a calcified primary complex is a common finding on chest CT studies in patients from an endemic area (Fig.…”
mentioning
confidence: 99%
“…Принципы выполнения резекций легких при раке основаны на результатах гистологического исследования удаленного регионарного лимфатического аппарата, которое информативно только в случае поражения ЛУ метастазами [9]. К сожалению, как в норме, так и при патологических состояниях определить направление лимфооттока легких прижизненно не удавалось, хотя предпринимались попытки анализа изменений во внутригрудных ЛУ при компьютерной томографии, в том числе у больных грибковыми заболеваниями легких [10]. Современная классификация регионарных внутригрудных ЛУ, применяемая в торакальной онкологии, предусматривает точное разграничение различных групп ЛУ корня легкого и средостения, причем необходимость удаления разных групп определяется локализацией первичной опухоли в той или иной доле легкого [11,12], что объясняется бóльшей частотой поражения метастазами именно этих групп ЛУ.…”
Section: результаты исследования и их обсуждениеunclassified